'Standing together – at a distance': Documenting changes in mental-health indicators in Denmark during the COVID-19 pandemic. Issue 1 (February 2021) - Clotworthy, Amy; Dissing, Agnete Skovlund; Nguyen, Tri-Long; Jensen, Andreas Kryger; Andersen, Thea Otte; Bilsteen, Josephine Funck; Elsenburg, Leonie K.; Keller, Amélie; Kusumastuti, Sasmita; Mathisen, Jimmi; Mehta, Amar; Pinot de Moira, Angela; et al.
Aims: There is a need to document the mental-health effects of the COVID-19 pandemic and its associated societal lockdowns. We initiated a large mixed-methods data collection, focusing on crisis-specific worries and mental-health indicators during the lockdown in Denmark. Methods: The study incorporated five data sources, including quantitative surveys and qualitative interviews. The surveys included a time series of cross-sectional online questionnaires starting on 20 March 2020, in which 300 (3×100) Danish residents were drawn every three days from three population groups: the general population ( N =1046), families with children ( N =1032) and older people ( N =1059). These data were analysed by trend analysis. Semi-structured interviews were conducted with 32 people aged 24–83 throughout Denmark to provide context to the survey results and to gain insight into people's experiences of the lockdown. Results: Absolute level of worries, quality of life and social isolation were relatively stable across all population groups during the lockdown, although there was a slight deterioration in older people's overall mental health. Many respondents were worried about their loved ones' health (74–76%) and the potential long-term economic consequences of the pandemic (61–66%). The qualitative interviews documented significant variation in people's experiences, suggesting that the lockdown's effect on everyday life had not been altogether negative. Conclusions: People in Denmark seem to have managed the lockdown without alarming changes in their mental health. However, it is important to continue investigating the effects of the pandemic and various public-health measures on mental health over time and across national contexts.